Listening to community: The aural dimensions of neighbouring. Issue 1 (January 2020) - Lewis, Camilla
This article examines the multisensory nature of everyday life and the ways in which sound shapes experiences of community, presenting findings from a research project, 'Place and belonging: What can we learn from Claremont Court housing scheme?' Whilst acknowledging the multisensory nature of perception, the discussion focuses on sound in particular, exploring the different ways that sound (or lack of it) informed residents' neighbouring practices and sense of community. Despite general fears of 'loss of community' due to increasing individualisation, the findings show the continued importance of neighbouring relations, which point to varied types of community attachment. Cases are presented from the data focusing on the themes of nostalgia, uncertainty and feelings of difference. These themes provide telling insights into the ways in which community is experienced and how people living in the same housing scheme interpret sounds differently. All residents were exposed to similar sound ecologies, but their significance and meanings were understood in vastly different ways. The article offers an original contribution by arguing that sound is an important dimension of everyday life in urban settings, which is related to affective and emotional dimensions of community, which have, as yet, been glossed over in the sociological literature.